Elastic analysis of rectilinear orthotropic composite circular plates subject to transversal and in-plane load conditions using Ritz method - Belardi, Valerio G.; Fanelli, Pierluigi; Vivio, Francesco (Composite structures, 2018)
An analytical procedure for the analysis of elastic behavior of rectilinear orthotropic composite circular plate subjected to orthogonal and in-plane loads is presented. This kind of plates is composed of fiber-reinforced layers featuring fibers, differently oriented, arranged along rectilinear trajectories; composite lay-ups commonly employed for spot junctions are considered. The constitutive equations for rectilinear orthotropic composite circular plates are derived in the frame of classical lamination theory. The displacement components are determined, according to a novel approach, applying Ritz method to the virtual displacements principle for the load conditions treated in this work. The proposed framework is an approaching step for the theoretical definition of a Spot Joint Element able to simulate spot junctions (bolts, rivets or generic pins) applied to composite plates. To this purpose, displacement constraints deriving from the theoretical reference model of Spot Joint Element are considered. The employment of these specific boundary conditions required the derivation of suitable approximation functions, here reported in parametric form. Analytical results obtained by using the proposed procedure precisely match numerical results obtained by using refined FE models, for different aspect ratios of the plate and different laminate symmetrical lay-ups.